Role of multiparametric prostate MRI in the management of prostate cancer - O'Connor, Luke P.; Lebastchi, Amir H.; Horuz, Rahim; Rastinehad, Ardeshir R.; Siddiqui, M. Minhaj; Grummet, Jeremy; Kastner, Christof; Ahmed, Hashim U.; Pinto, Peter A.; Türkbey, Barış (Springer, 2021)
Introduction Prostate cancer has traditionally been diagnosed by an elevation in PSA or abnormal exam leading to a systematic transrectal ultrasound (TRUS)-guided biopsy. This diagnostic pathway underdiagnoses clinically significant disease while over diagnosing clinically insignificant disease. In this review, we aim to provide an overview of the recent literature regarding the role of multiparametric MRI (mpMRI) in the management of prostate cancer. Materials and Methods A thorough literature review was performed using PubMed to identify articles discussing use of mpMRI of the prostate in management of prostate cancer. Conclusion The incorporation of mpMRI of the prostate addresses the shortcomings of the prostate biopsy while providing several other advantages. mpMRI allows some men to avoid an immediate biopsy and permits visualization of areas likely to harbor clinically significant cancer prior to biopsy to facilitate use of MR-targeted prostate biopsies. This allows for reduction in diagnosis of clinically insignificant disease as well as improved detection and better characterization of higher risk cancers, as well as the improved selection of patients for active surveillance. In addition, mpMRI can be used for selection and monitoring of patients for active surveillance and treatment planning during surgery and focal therapy.
Keywords: Prostate Cancer; Multiparametric MRI (mpMRI); Fusion Biopsy; Active Surveillance; Prostatectomy